Dynamics of a predator-prey model incorporating infectious disease and quarantine on prey - Lahay, Anatasya; Payu, Muhammad Rezky Friesta; Mahmud, Sri Lestari; Panigoro, Hasan S; Zakaria, Perry (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
In this article, the dynamics of a predator-prey model incorporating infectious disease and quarantine on prey population is discussed. We first analyze the existence conditions of all positive equilibrium points. Next, we investigate the local stability properties of the proposed model using the linearization method. We also determine the basic reproduction number using the next generation matrix. Finally, some numerical simulations are performed to validate the stability of each equilibrium point.